Managing for the future - Drucker, Peter F. (Peter Ferdinand) 1909-2005 (Butterworth-Heinemann, 1992)
This wide-ranging, future-oriented book is sure to number among the most important and influential business books of the decade. Drucker writes with penetrating insight about the critical issues facing managers in the 1990s: the world economic order; people at work; new trends in management and the governance of organizations.